Modificación de un protocolo J-SYNCH sobre la tasa de preñez de vacas cebú con cría al píe - Veliz Patiño, Junior José (2022)
The objective of the research was to evaluate the effect of proestrus prolongation with a modified J-Synch treatment of 7 days of progesterone on pregnancy rate and hormone levels in Zebu cows with calves at foot. Cows (n= 200) were used to represent the experimental units. Two groups were formed for the following: group 1 was formed with the J-synch protocol (n=100) and group 2 with the conventional protocol with estradiol cypionate (n=100). All data from this research were analyzed using the Generalized Linear Mixed Models (MLGM) procedure for families of binary data with logit link to determine significant differences (p<0.05). The 7-day J-Synch treatment generated a higher pregnancy rate (p=0.04) (62.0%) than the conventional one (40.0%). Progesterone levels were higher in the 7-day J-Synch cows (4.4 ng/mL), while estradiol levels were similar between groups. The 7-day J-Synch treatment is a viable alternative for the correct synchronization of heat in zebu cattle with calves at the foot.